Factors related to respiratory and cardiovascular symptoms in the United Kingdom. Issue 2 (June 1978) - Dean, G; Lee, P N; Todd, G F; Wicken, A J; Sparks, D N
Abstract : Factors related to eight respiratory and cardiovascular symptoms have been studied in a sample of 12 736 men and women aged 37 to 67 living in England, Scotland and Wales. The prevalence of each of these symptoms was independently associated with increasing age, with lower social class, with living in wales, and with exposure at work to fumes or to dust, especially in mines or quarries. Prevalence of some symptoms was also increased in those who were divorced, separated or widowed, who took less exercise or who were seriously over or under weight. Respiratory symptoms increased with the number of cigarettes smoked, with level of inhalation, and with the smoking of plain rather than filter cigarettes, though the last two associations were significant only for some symptoms. Smokers who had given up for five years or more had levels of symptoms similar to those who had never smoked, while pipe and cigar smokers had markedly fewer symptoms than cigarette smokers. The relationship between smoking and cardiovascular symptoms was not as clear as the relationship between smoking and respiratory symptoms.